ANALISIS WACANA JURNALISME KEBERAGAMAN DALAM PEMBERITAAN KAWASAN KULINER PECINAN (KKP) DI HARIAN FAJAR - Dian Muhtadiah Hamna; Muhammad Tahir (Jurnal Dakwah Tabligh, 2019)
In the era of democracy, the issue of diversity becomes interesting to be discussed given the importance of maintaining the integrity of the Unitary Republic of Indonesia (NKRI). One of the roles of the media is to be a bridge to convey the discourse of diversity in a pluralist Indonesian society. Through diversity journalism, the media has a role in bringing messages of peace and not confusing the atmosphere of conflict through reporting. News dictionaries play an important role in constructing people's perception of an event. One of the diversity journalism was applied by Fajar Daily through the reporting of the Chinatown Culinary Area (KKP) in Makassar. The consistency of peaceful reporting makes the area visited by interethnic residents. The long-term goal of this research is to find out how diversity journalism reconstructs people's perceptions so that they are motivated to create harmony in the midst of multipluralism. It also serves as a guide for the media and journalists in maintaining messages of peace through the news. While the specific target to be achieved is to test the agenda-setting theory and the theory of discourse analysis in the preaching of the KKP in Fajar Daily.